HYDROTHERMAL AND SUPERGENE CLAYS OF THE OKLO NATURAL REACTORS: CONDITIONS OF RADIONUCLIDE RELEASE, MIGRATION AND RETENTION - Pourcelot L.; Gauthier-Lafaye F. (My University, 1999)
Mineralogical, chemical and O-isotopic analyses were performed on the clay matrices surrounding two natural fission reactors of the Oklo deposit. In the deeply preserved reactor 10 (450 m), clays are composed of hydrothermal Mg-chlorites and sudoites (Al-chlorites). The wide range of their O-isotopic compositions (from 0.0 to 15.1%% SMOW) is consistent with crystallisation during conditions of criticality, when the reactors created a thermal gradient of 100°C/m. The temperature in the core of reactor is calculated to have been approximately 400°C. In contrast, in the shallow reactor 9 (120 m deep), vermiculitized Al-chlorites are the products of the weathering of the hydrothermal chlorites. These vermiculitized Al-chlorites are 18O enriched (δ18O=18%% SMOW) and underwent interaction with surface fluids (-2 to -5%%). 149Sm/147Sm isotopic ratios of the clays of reactor 9 show a wide dispersion (2-3 m) of the fissiogenic Sm around the reactor. The migration of the fissiogenic Sm, which is usually retained in the deep reactors, is here related to the circulation of meteoric water under oxidising conditions.
Keywords: OKLO; NUCLEAR WASTE; CLAYS; WEATHERING; O-ISOTOPES; FISSION PRODUCTS